Beyond reporting: how external stakeholders and strategic posture shape ESG disclosure in Malaysia - Boon, Heng Teh; Wong, Wai-Khuen; Tan, Siow-Hooi (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
This study aimed to investigate the impact of a company’s strategic posture on the relationship between stakeholder power and ESG (Environmental, Social, and Governance) disclosure. By employing multivariate panel data regression techniques, this study analysed the direct and indirect effect of strategic posture on the relationship between stakeholder power and ESG disclosure. The research relied on a panel data set comprising 71 Malaysian companies observed from 2013 to 2022. The ESG orientation score, selected as proxy of strategic posture, was derived from computer-aided textual analysis of chairpersons’ statements published in financial annual reports. The dataset also consisted of ESG disclosure scores and firm-related data from Bloomberg. The mediation analysis revealed that a company’s strategic posture significantly mediated the influence of stakeholder power on ESG disclosure. Empirical findings provide new insights on the oftenunderstudied role of external stakeholders who impact a company’s strategic orientation and, consequently, its ESG outcomes. This study provides practical guidance for decisionmakers to prioritise external ESG demands while emphasising the importance of engaging with powerful stakeholders for impactful ESG reporting. This study contributes to the literature by exploring strategic posture as a mediator in clarifying the relationship between stakeholder power and ESG within a developing country context.